In vitro visualization and quantitative characterization of Pseudomonas aeruginosa biofilm growth dynamics on polyether ether ketone. Issue 10 (7th January 2022) - Spake, Carole S. L.; Berns, Ellis M.; Sahakian, Lori; Turcu, Adrian; Clayton, Ahsia; Glasser, Jillian; Barrett, Caitlin; Barber, Douglas; Antoci, Valentin; Born, Christopher T.; Garcia, Dioscaris R.
Abstract: Prevention and treatment of orthopedic device‐related infection (ODRI) is complicated by the formation of bacterial biofilms. Biofilm formation involves dynamic production of macromolecules that contribute to the structure of the biofilm over time. Limitations to clinically relevant and translational biofilm visualization and measurement hamper advances in this area of research. In this paper, we present a multimodal methodology for improved characterization of Pseudomonas aeruginosa grown on polyether ether ketone (PEEK) as a model for ODRI. PEEK discs were inoculated with P. aeruginosa, incubated for 4−48 h time intervals, and fixed with 10% neutral‐buffered formalin. Samples were stained with fluorescent dyes to measure biofilm components, imaged with confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM), and quantified. We were able to visualize and quantify P. aeruginosa biofilm growth on PEEK implants over 48 h. Based on imaging data, we propose a generalized growth cycle that can inform orthopedic diagnostic and treatment for this pathogen on PEEK. These results demonstrate the potential of using a combined CLSM and SEM approach for determining biofilm structure, composition, post‐adherence development on orthopedic materials. This model may be used for quantitative biofilm analysis for other pathogens and other materials of orthopedic relevance for translational study of ODRI.